Flight #116 is down - Cooney, Caroline B. (New York : Scholastic, 1992)
Teenager Heidi Landseth helps rescue people from a plane crash on her family's property, and the experience changes her life forever.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
6.7
5-8
7-9
Keywords: Aircraft accidents -- Fiction; Aircraft accidents -- Fiction